SKEPTISME PROFESIONAL MEMEDIASI HUBUNGAN INDEPENDENSI DENGAN KEMAMPUAN AUDITOR MENDETEKSI KECURANGAN - Mustarikah, Anik (Prodi Akuntansi FEB UNITOMO, 2018)
This research is provide empirical evidence of the direct and indirect effect of independency toward auditor’s ability to detect fraud with professional skepticism as a mediator. This sample ini this study are 90 person as internal auditors working at Badan Pengawasan Keuangan dan Pembangunan (BPKP) throughout Indonesia. The method of analysis used is descriptive statistics, hypothesis test using approach Partial Least Square (PLS) with WarpPLS version 6.00 software through measurement inner model and outer model. The result of this study prove that the direct effect of independency has significant influence on auditor’s ability to detect fraud. However the indirect effect of independency is not affected to auditor’s ability to detect fraud with professional skepticism as a mediator.